Ivan Minaev’s Sketches of Ceylon and India: A Russian Perspective on Nepal - Rebecchini, Damiano (Prithvi Academic Journal, 2023)
Ivan Minaev (1840-1890) was one of the first great Russian Indologists and students of Buddhism. Between 1874 and 1886, he made three long journeys in which he visited Ceylon, India, Burma and Nepal. Thanks to his profound knowledge of the classic (Sanskrit and Pali) and modern languages of the Indian subcontinent, he had the opportunity not only to read ancient works, but also to meet government and elite figures as well as the people. This paper focuses in particular on Minaev's depiction of Nepal in a series of travel notes such as Ocherki Tsejlona i Indii (Eng. trans. Sketches of Ceylon and India, 1878) and in a number of essays. Aware of the military and ideological clash between England and Russia that was taking place in Central and South Asia, Minaev took an original stance towards the British colonial domination: he supported the need for the Russian government to imitate the British Empire in building important infrastructures (roads, bridges, railways), but, with regard to Nepal, he emphasises the importance of respecting the appalling richness, variety and originality of its languages, religious rites, legends and songs, which are preserved in a much uncontaminated form here than in India.